(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mostly in the process control industries, the main issue well-known in the literature is to control the non-linear process. The major problem lies on control of the liquid level in a spherical tank, which is non-linear in nature because of the variation in cross section area resulting in the change of shape. System identification is done using black box model and it is nonlinear along with the worst case model, parameter criterion which is approximated to first order plus dead time delay. Newton’s Forward interpolation based Proportional Integral controller is implemented in the control of the non-linear process. The real time work is done in MATLAB via VMAT-01 module. The servo and regulatory responses of NF based proportional integral controller for different operating region is noted and results are compared with the other numerical methods such as Dimensional Analysis method and weighted geometric Centre method. The better controlling method is determined based on the indices such as reduced overshoot, faster settling time, better set point tracking, disturbance rejection and lower performance indices.